An experimental study of the effects of elicitation methods on review of preliminary audit strategy by external auditors* - BORITZ, J.E.; GABER, B.G.; LEMON, W.M. (Contemporary Accounting Research, 1988)
This paper reports the results of an empirical investigation of auditor judgment involving the assessment of audit risk and planning of an audit strategy. The study focuses on whether methodological techniques used for conducting research affect decision behavior; in particular, whether silent versus think‐aloud elicitations of auditor responses lead to different responses. Auditors performed the experimental tasks under two methods of eliciting responses: they responded to half of the cases silently, and to the other half while thinking aloud into a tape recorder. Comparisons of the silent and aloud responses suggest a systematic influence exerted by method of eliciting responses, but one which varies depending on the subjects' positions in the firm and the particular judgment being made. Résumé. Il est question dans le présent article des résultats d'une étude empirique des jugements portés par le vérificateur sur l'évaluation du risque lié à la vérification et la planification d'une stratégie de vérification. L'étude traite des répercussions des techniques méthodologiques utilisées dans le cadre de la recherche sur le comportement décisionnel; elle vise en particulier à déterminer si les réponses des vérificateurs diffèrent selon le mode d'expression, en silence ou à voix haute. Dans le cadre de cette étude, les vérificateurs participants ont accompli les tâches expérimentales en communiquant leurs réponses selon deux modes d'expression: en silence pour la moitié des cas et à voix haute pour l'autre moitié, avec enregistrement sur bande. La comparaison des deux séries donne lieu de croire que le mode de communication des réponses exerce une influence systématique, mais une influence variable selon le poste occupé par le sujet au sein du cabinet et selon le jugement précis qu'il porte.